The Overview of Problems Learned in Higher Education Institutions - Zohaib Hassan Sain; Muslem Daud; Nyak Mutia Ismail; Sabrina Sabrina; Wahyu Khafidah (International Conference on Multidisciplinary Research, 2022)
The purpose of this study is based on exploratory research to identify “Challenges in Quality of Education in HEIs of Pakistan”. The exploratory research approach is used to achieve the objectives of the study in less time and with inexpensive means. For the last few years, Pakistan is facing a lot of challenges in the education sector such as curriculum, few training institutions, corruption in education, teachers’ behavior, and less research work. Emerging Issues in the education sector are fewer training institutions and the trend toward research work which is essential to follow for the growth and strength of any economy. The purpose of our research is to identify the major challenges in the educational sector in Pakistan which the educational sector is suffering for the last few years. The researcher used triangulation to carry out the reliability and validity of the data for results. So, to conduct this triangulation the researcher used questionnaires for the students, questionnaires for the teachers, and interviews with the management. . In this regard primary data was collected from the focused group of students using a sample of 100 questionnaires for each university filled by the students of the selected five universities. The findings highlight the positive relationship of quality education with curriculum, few training institutions, corruption in education, teachers’ behavior, and less research work. These challenges caused restrictions in accomplishing competent teaching and learning with respect to quality education. According to the current situation in Pakistan, the same challenges are being faced. Keywords: Curriculum, Corruption, Teacher’s Behavior, Research Work.